Peran Media Massa Sekjen DPR RI Dalam Program Berita "TVR 17" - Yonarisman Muhammad Akbar (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
This research examines the role of mass media applied by TVR Parliament, which is part of the Secretariat General of the DPR RI, through a flagship news program entitled "TVR 17". This research aims to understand the communication approach used in delivering up-to-date information about parliamentary activities to the public. The research method involved content analysis, interviews, and observation of the production and broadcast of "TVR 17". The results of this study are expected to provide an in-depth insight into the role of TVR Parliament mass media in increasing public understanding and participation in the legislative process and public policy. The implications of these findings can make an important contribution in optimizing the role of parliamentary media as a means of transparency and democratic participation in Indonesia.